Student-Centred Pedagogical Approach and Student Engagement at a Private University in Western Uganda - Mugizi, Wilson; Katuramu, Abeera Odetha; Ogaga Dafiewhare, Augustina; Kanyesigye, John (Education Journal, 2021)
This study investigated the relationship between the student-centred pedagogical approach and student engagement at a private university in Western Uganda. The student-centred approach was studied in terms of active learning, contextual learning, motivation of learners and collaborative learning. On the other hand, student engagement was conceptualised in terms of behavioural, affective, cognitive and agentic engagements. The study adopted the cross-sectional research design on a sample of 264 undergraduate students. Data were collected using a self-ad mistered questionnaire and analysed quantitatively. Descriptive analysis showed that students rated their levels of engagement and lecturers use of the student-centred approach as high on all aspects. Regression analysis revealed that the student-centred approaches of active learning, contextual learning, motivation of students and collaborative learning had a positive significant relationship with student engagement. It was concluded that the teacher-centred pedagogical approaches namely; active learning, contextual learning, motivation of students and collaborative learning are imperative for promotion of student engagement. Therefore, it was recommended that university lecturers should promote the use of those approaches when conducting teaching in universities.
Keywords: Active; Affective; Agentic; Behavioural; Cognitive; Contextual; Collaborative; Motivation; Student-Centred; Student Engagement